Exploring nutrient-sensitive landscape configurations for rural communities in southern Mexico - Novotny, Ivan P.; Rossing, Walter A.H.; Tittonell, Pablo Adrian; Fuentes-Ponce, Mariela H.; Groot, Jeroen C.J. (Elsevier, 2024)
In Mexico, the traditional MILPA polycropping system is giving way to maize monocultures, impacting the nutritional diversity of smallholder farmers and diminishing ecosystem services. This study explores landscape alternatives to enhance nutritional self-sufficiency and environmental performance in rural communities, comparing scenarios without (S1) and with (S2) innovative cropping systems. The innovations, maize-squash and MIAF (a variation of MILPA with fruit trees), were evaluated using the LandscapeIMAGES modeling framework in two Oaxacan municipalities: Santa Catarina Tayata (SCT) and San Cristóbal Amoltepec (SCA). The assessment considered nutritional elements, ecosystem services proxies, labor requirements, and income associated with various land-use options. In scenario S1, nutritional self-sufficiency was achievable in SCT but not in SCA, even with a 17% expansion of agriculture into forest and grassland areas. Scenario S2, incorporating maize-squash and MIAF, facilitated nutritional self-sufficiency in both municipalities, while concurrently boosting incomes, carbon stocks, and reducing soil erosion. This research underscores the potential of reshaping landscapes in small communities to address widespread issues like nutritional gaps and inadequate natural resource conservation. By emphasizing innovative cropping systems, the study provides positive solutions to enhance the well-being of smallholder farmers and promote sustainable land use practices in the face of evolving agricultural trends.